PENERAPAN METODE TALAQQI AYAT AL-QUR’AN DALAM MENINGKATKAN DAYA HAFALAN SISWA TERHADAP MATA PELAJARAN TAHFIDZUL QUR’AN KELAS VII DI SMP IT AZZAKIYATUSHOLIHAH - Nisa Nurhidayah; Nuruddin Araniri; Herdianto Waluyo Pratomo (Program Studi Pendidikan Agama Islam, Universitas Majalengka, 2021)
Memorizing the Qur'an is a very noble act and is closely related to one's memory (memory) and is very dependent on the ability of reason. By memorizing the Qur'an a person will get used to remembering every letter, word and sentence, it becomes easy to understand its contents. But in reality there are still many students who find it hard and difficult to memorize so that guidance from a teacher is still needed to justify makhraj, and tajwid, and there are still many students who often forget the memorization that has been memorized because of the student's ability to memorize the Qur'an. Therefore, it is necessary to have the right method from the many methods of memorizing the Qur'an. One of the schools that has subjects to memorize the Qur'an using the talaqqi method is SMP IT Azzakiyatussholihah, where the requirement for graduating from school is to memorize at least 5 juz of the Qur'an.This research uses qualitative research with descriptive method, where this research is used to investigate, find, describe, and explain something data obtained from observations, interviews and documentation. The location of this research is IT Azzakiyatussholihah Middle School, Campaga Village, Talaga District, Majalengka Regency with data sources from the principal, tahfidz teacher.The results of the study after conducting research using several of the methods above, the authors concluded that the application of the talaqqi method in improving students' memorization power for learning tahfidzul Qur'an at SMP IT Azzakiyatussholihah was carried out in several steps, namely: adding new memorization, muroja'ah memorization and evaluation. The memorization process using the talaqqi method is the most appropriate method to use, this is evidenced by the repetition of readings and examples read by the teacher so that the strength and memorization power will be stronger, and the results are very good, so students are very enthusiastic in participating in the learning process, even though There are still weaknesses and strengths of several factors, but they are not used as an obstacle to the learning process.